Influence of Retail e-Commerce Website Design on Perceived Risk in Online Purchases - García-Salirrosas, Elizabeth (2022)
The objective of this study was to estimate the influence of the perception of the web design of e-commerce retail on the level of risk perceived in online purchases by consumers. For this, a cross-sectional study of causal relationship was carried out through the structural equation model (SEM). The sample consisted of 390 consumers (54.9% women and 45.1% men) in an age range of 18 to 67 years. For the validation of the instrument, the exploratory factorial analysis (EFA) and the confirmatory factorial analysis (CFA) were applied. In turn, the latter was also used to contrast the study hypothesis. An inverse and significant relationship was demonstrated between the research variables (p<0.001 and R= -0.65). This means that the better consumers’ perception of online retail website design, the lower the perceived risk of shopping online.